2020
DOI: 10.21577/0103-5053.20190221
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effect of Inhibitors Solutions on the Chemical Composition of Waxes by Rheology Tests and High Resolution Mass Spectrometry

Abstract: Wax deposit is of a great concern in the petroleum industry and causes partial or total blockage of the pipelines. In this work, four Brazilian crude oils (P1-P4) and five inhibitors solutions (I1-I5) were used associating rheology results to understand, at a molecular level, the characteristics of the saturated fractions by high-resolution mass spectrometry (Orbitrap coupled to atmospheric pressure chemical ionization (APCI) source) and two-dimensional gas chromatography coupled to mass spectrometry (GC × GC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…The FT-ICR MS analyses were performed by a SolariX 9.4T FT-ICR mass spectrometer (Bruker, Bremen, Germany) equipped with an ICR cell as the infinity cell.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FT-ICR MS analyses were performed by a SolariX 9.4T FT-ICR mass spectrometer (Bruker, Bremen, Germany) equipped with an ICR cell as the infinity cell.…”
Section: Methodsmentioning
confidence: 99%
“…The maximum acceptable accuracy was 3 ppm. The Composer and Compass Data Analysis presents information about the heteroatom classes present in the samples, DBE information, and charts relating carbon number and DBE values. The DBE is calculated from eq . where C represents the number of carbons, H the number of hydrogens, N the number of nitrogens in the molecular formula.…”
Section: Methodsmentioning
confidence: 99%
“…Romão et al used four Brazilian crude oils (P1-P4) and five inhibitor solutions (I1-I5), combined with rheological results, to understand the characteristics of saturated fractions at the molecular level by HRMS (Orbitrap-coupled APCI source) and GC × GC-MS, and to relate the results of rheological tests to the properties of saturated fractions. The experimental results revealed that inhibitor I1 favored the inhibition process of paraffins when oils have smaller and monocyclic saturated chain hydrocarbon profiles, whereas for oils with larger amounts of polycyclic chain hydrocarbons, the inhibitor I4 appeared to be the alternative [93]. Dong et al developed a comprehensive and in-depth UHRMS analytical method (APCI-Orbitrap Fusion MS) for the production process of Liaohe Petrochemical lubricants.…”
Section: Uhrms Characterization Of Hydrocarbons In Different Complex ...mentioning
confidence: 99%
“…Lubricant base oils; 166 Asphaltene fractions; 193,194,[231][232][233][234] Bitumen; 235 S-containing compounds; 28,182,232,[236][237][238][239] polychlorinated naphthalenes (PCNs); 225 polycyclic aromatic hydrocarbons (PAHs); 28,78,226,233,240 Cycloalkanes; 78,241,242 Steroids compounds; 243 N-, O-containing compounds 28,206,232,244,245 More suitable for non-polar samples than ESI but less than APPI. Thermal degradation and fragmentation are problems.…”
Section: Apci (Atmospheric Pressure Chemical Ionization)mentioning
confidence: 99%